Multimodal therapeutic strategies against gastric cancer: from conventional treatments to tumor microenvironment targeting - Yuan, Xi; Chen, Changxian; Pang, Yixuan; Wang, Xuanzhi; Yang, Tingting; Long, Anying; Liang, Na; Yang, Ying; Li, Chunming (Frontiers in Immunology, 2025)
Gastric cancer is one of the most common malignant tumors of the digestive system, with persistently high global morbidity and mortality rates. The multi-level heterogeneity of the gastric cancer tumor immune microenvironment (TIME) is closely associated with treatment efficacy and prognosis. This heterogeneity is reflected not only in the types and functions of various cells within the microenvironment but also in multiple aspects such as molecular profiles, metabolic pathways, and the spatial distribution of tumor cells. Currently, the interaction between gastric cancer and its microenvironment, as well as the resulting immune evasion, has become a research hotspot. This article reviews the role of cellular heterogeneity and metabolic reprogramming in the gastric cancer Tumor Immune Microenvironment (TIME) in reshaping the immune microenvironment, and summarizes traditional therapies alongside existing and potential microenvironment-modulating treatment strategies.